Природне відновлення сосни кримської (Pinus pallasiana D. Don) на залізорудному відвалі Криворіжжя - Korshikov, I.I.; Krasnoshtan, O.V.; Terlyga, N.S.; Mazur, A.E. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
The article provides a description of renewal phenomenon of Pinus pallasiana D. Don on iron ore dumps in Kriviy Rig region. The phenomenon takes place around 25–30 year old stands of this species which were formerly planted during the reclamation of the dump. The area of P. pallasiana introduction micropopulations forming of the dump exceeds tenfold that of initial stands. Vital state of self sown stand is good. Its age composition varies from 2 to 10 years, the density being 7–80 specimens per 100 m2.